Effect of moderate and high intensity training sessions on cardiopulmonary chemosensitivity and time-based characteristics of response in high performance rowers - Tomiak Tomasz (Baltic Journal of Health and Physical Activity, 2014)
Background: The present study was performed to clarify fatigue-induced effects of a strenuous and moderate intensity endurance training session on temporary changes of cardiopulmonary (CP) chemosensitivity and fast kinetics response.